The Role of Work Stress and Working Environment on Employee Turnover Intention in Mining Company - Ris Akril Nurimansjah; Ni Luh Kardini; Mulyadi; Syech Idrus; Abdurohim (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2023)
This study sought to ascertain the impact of workplace stress and intention to leave on employee turnover. All of the employees at one of the mining businesses in Indonesia made up the population of this study, which had a total sample of 35 employees. Based on the saturated sample approach, samples were obtained. Multiple linear regression analysis is the technique utilized for data analysis. The study's findings indicate that employee turnover intentions are significantly influenced by both the work environment and work stress, either simultaneously or in part. The following conclusions can be taken from the data that was gathered and tested using the multiple linear regression model: The workplace has a considerable impact on employee turnover intention, with a t-test result of 0.000. The findings of the t test, which showed a value of 0.049, on the intention of employee turnover, show that work stress has a substantial impact. According to the results of the f test, the workplace environment and work stress have a considerable impact on the likelihood that employees will leave their jobs.